Aberrant Claustrum Microstructure in Humans after Premature Birth. (25th June 2021) - Hedderich, Dennis M; Menegaux, Aurore; Li, Hongwei; Schmitz-Koep, Benita; Stämpfli, Philipp; Bäuml, Josef G; Berndt, Maria T; Bäuerlein, Felix J B; Grothe, Michel J; Dyrba, Martin; Avram, Mihai; Boecker, Henning; et al.
Abstract: Several observations suggest an impact of prematurity on the claustrum. First, the claustrum's development appears to depend on transient subplate neurons of intra-uterine brain development, which are affected by prematurity. Second, the claustrum is the most densely connected region of the mammalian forebrain relative to its volume; due to its effect on pre-oligodendrocytes, prematurity impacts white matter connections and thereby the development of sources and targets of such connections, potentially including the claustrum. Third, due to its high connection degree, the claustrum contributes to general cognitive functioning (e.g., selective attention and task switching/maintaining); general cognitive functioning, however, is at risk in prematurity. Thus, we hypothesized altered claustrum structure after premature birth, with these alterations being associated with impaired general cognitive performance in premature born persons. Using T1-weighted and diffusion-weighted magnetic resonance imaging in 70 very preterm/very low-birth-weight (VP/VLBW) born adults and 87 term-born adults, we found specifically increased mean diffusivity in the claustrum of VP/VLBW adults, associated both with low birth weight and at-trend with reduced IQ. This result demonstrates altered claustrum microstructure after premature birth. Data suggest aberrant claustrum development, which is potentially related with aberrant subplate neuron and forebrain connection development of prematurity.